Methodology for Valuing the Health Impacts of Air Pollution : Discussion of Challenges and Proposed Solutions - Narain, Urvashi; Sall, Chris (World Bank, Washington, DC, 2016)
This report is meant to inform a joint publication by the World Bank and Institute for Health Metrics and Evaluation (IHME) on the economic costs of air pollution. Air pollution is a global challenge and one that is acutely felt in developing countries. Illnesses caused by ambient and household air pollution claim the lives of nearly 6 million people each year. The goal of the joint World Bank-IHME report is to raise awareness about the severity of this challenge and to strengthen the business case for countries to take action on reducing air pollution. A secondary goal of the joint World Bank-IHME report is to further the development of a consistent framework for valuing the costs of air pollution in World Bank operations. This report serves as a background paper for the joint report and provides a detailed discussion of the key methodological choices that must be made in valuing the health impacts of pollution and makes recommendations on how these challenges can be addressed. While past efforts to value the health impacts of pollution have greatly contributed to the discussion of challenges and potential solutions, they have at the same time made a number of methodological choices on an ad hoc basis. The hope in developing this note is to bring greater clarity to what the issues are and to provide guidance on how they can be addressed consistently (the note provides clear recommendations where possible and a framing of issues where the literature or the context does not as yet provide clarity on potential solutions).